Application of respiratory muscle training for improved intermittent exercise performance in team sports: a narrative review - Kowalski, Tomasz; Dias Rodrigues, Gabriel; Zanini, Michele (Frontiers in Sports and Active Living, 2025)
Since traditional, sport-specific training or exercise programs lack sufficient stimulus to improve the function of the respiratory muscle, the rationale for integrating additional respiratory muscle training (RMT) emerged. RMT has the potential to improve intermittent exercise performance in team sports athletes, as proven in multiple studies. This narrative review aims to provide coaches with tools to select the appropriate form of RMT, tailored to the athletes’ needs, using appropriate diagnostic methods, intervention protocols, and devices. Common protocols may include performing 30 inspiratory maneuvers twice a day, five days a week, with resistance-based trainers or engaging in 20–40 min of vigorous ventilation with isocapnic devices every other day. Most of the interventions that positively influence intermittent exercise performance employed inspiratory pressure threshold loading, lasted 6–8 weeks, and relied on a high frequency of training sessions, progressive overload, and relatively high initial resistance (starting intensity). Less-investigated RMT methods, such as tapered flow resistive loading or voluntary isocapnic hyperpnea, should be analyzed in the context of intermittent exercise performance. Moreover, further research addressing RMT and hypoxia, between-gender differences, and athletes with disabilities seems warranted.